Politik Hukum Pemulihan Aset Tindak Pidana Ekonomi: Sinkronisasi Norma Asset Recovery demi Menjaga Stabilitas Keuangan Negara - Nadia Nabela; Andi Srikandi MPB (PATTIMURA Law Study Review, 2026)
Economic crimes have triggered massive illicit capital flight, undermining the state's fiscal capacity and financial stability. Although asset recovery has become a global priority, Indonesia's legal framework remains ineffective in confiscating and recovering illicit assets. This study analyzes the structural fragmentation of Indonesia's asset recovery regulatory framework and evaluates its macroeconomic implications for the country's financial stability. Employing doctrinal legal research, the study applies statutory, conceptual, and comparative approaches, integrated with the Economic Analysis of Law framework. The findings reveal a severe disharmony between the in personam (conviction-based) and in rem (property-based) asset recovery regimes embedded in various sectoral laws, resulting in institutional fragmentation and sectoral rivalry. From an economic perspective, these normative conflicts generate high transaction and asset maintenance costs, leading to significant asset depreciation and a low asset recovery rate, ultimately imposing substantial losses on the State Budget (APBN). The study highlights the urgent need for a coherent and integrated asset recovery framework to enhance legal effectiveness, safeguard state finances, and strengthen Indonesia's fiscal resilience.